Valoración de los tres pilares del desarrollo sostenible del turismo que se aplican en la zona del casco urbano de la ciudad de Iquitos, Perú - Alva Del Águila, Kiara Sarahi (2023)
The thesis "Assessment of the three pillars of sustainable development of tourism that are applied in the urban area of the city of Iquitos, Peru", the research was developed in the urban area of the city of Iquitos capital of the Peruvian Amazon, with methodology under a quantitative approach with descriptive design. The technique was the survey of closed questions according to the Likert scale with 5 alternative answers. The sample consisted of 50 surveys applied to tourism and environmental actors from state institutions and private companies that are related to the object of study. The three pillars of sustainability were studied: the indicators studied were: environmental, socio-cultural and economic. The descriptive hypothesis was demonstrated, the results give results from regular downwards; It is admitted that the sustainability of tourism in the study area is very low, it is very likely that the tourism actors have the objective reality of the problem, it is suggested that complementary indicators to this study should continue to be studied.